2004
DOI: 10.1063/1.1781363
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteric liquid-crystal laser as an optic fiber-based temperature sensor

Abstract: In this work, we have studied the temperature dependence of a cholesteric liquid-crystal laser coupled to an optical fiber, with a view towards optical fiber sensor applications. To stabilize the laser emission, we developed a procedure to align the liquid crystal placed in the fiber. Unexpected oscillations in the laser emission were observed as the temperature was varied, which can be understood in terms of the competition between bulk and surface anchoring torques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(69 citation statements)
references
References 17 publications
1
64
0
4
Order By: Relevance
“…However, the proper understanding some of its basic features has appeared much later, when the interest in lasing in LC systems has been renovated [2][3][4][5][6][7][8][9][10][11]. The current interpretation of the effect is based on the photonic band-gap concept [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the proper understanding some of its basic features has appeared much later, when the interest in lasing in LC systems has been renovated [2][3][4][5][6][7][8][9][10][11]. The current interpretation of the effect is based on the photonic band-gap concept [2].…”
Section: Introductionmentioning
confidence: 99%
“…They can be made in a form of polymer films [8,9]. The sensitivity of LCs to external factors such as temperature, electric and magnetic fields is a promising feature for creating different lasing sensors [10]. The low threshold of the effect in CLC allows for the cascade excitation of the lasing emission, when subsequent LC cell is pumped by lasing from the previous one [11].…”
Section: Introductionmentioning
confidence: 99%
“…With the first demonstration of a CLC fiber laser for sensor application [16], research is needed at the technological front, to enable the design and optimization of CLC lasers. In this paper, we report the results of our study of the dependence of the lasing threshold on dye concentration and liquid crystal sample thickness in dye-doped CLC lasers.…”
Section: Introductionmentioning
confidence: 99%
“…The pitch, the distance over which the director field rotates by 2π radians, is sensitive to external stimuli such as temperature, light, electric field, and mechanical stress [20][21][22][23][24][25]. Kurihara et al have reported on the photochemical change in transparency as well as the selective reflection of a cholesteric LC (ChLC) resulting from the photoisomerization of a chiral azobenzene compound doped in a host nematic LC [26][27][28][29][30][31].…”
Section: Cholesteric Lcmentioning
confidence: 99%